Current trends in physical and physiological profile of elite WKF karate athletes: A systematic review - Gawel, E.; Drozd, M.; Zajac, A. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This qualitative analysis aimed to: identify the physical and physiological factors that characterize elite WKF kumite and kata athletes, identify testing protocols that are used to examine the above mentioned profiles of WKF karatekas and indicate the variables that are significant for elite-level performance.